German Perspective on 6G – Use Cases, Technical Building Blocks and Requirements Insights by the 6G Platform Germany - Franchi, Norman; Dressler, Falko; Ergenc, Doganalp; Guter, Paulus; Lassen, Vincent; Lübke, Maximilian; Veihelmann, Christian Tobias; Baradie, Shaden; Bassbouss, Louay; Bathelt, Andreas; Eichhorn, Fabian; Fink, Lucas; et al. (FAU University Press, 2024)

Multilevel Codes in Lattice-Reduction-Aided Equalization - Fischer, Robert F.H.; Huber, Johannes; Stern, Sebastian; Guter, Paulus (International Zurich Seminar on Information and Communication (IZS 2018), Zurich, Switzerland, 2018)
The application of multilevel codes in lattice-reduction-aided equalization is considered, i.e., the decoding of multilevel codes when (Gaussian) integer linear combinations of the codewords in signal space are present. Typically, multilevel codes do not generate lattice codes, hence arbitrary integer linear combinations are not directly decodable. We show that this lattice property is not required, which relaxes the constraints on the component codes significantly. A generalized version of multistage decoding which incorporates a “carry correction” is proposed; it circumvents the lattice property and any integer linear combinations are decodable. Numerical simulations are given to cover the performance of the proposed method.<br